Engineering A Nation: The Life and Career of M. Vishveshwaraya(1861-1962) - Aparajith Ramanath (Haryana Penguin Random House, 2024)
All
MIR No.: 196
Order Date: 2024-10-16
Order No: CU/OPEX/LIBRARY/41/2024-25
Received Date: 2024-10-30
Keywords: Engineering, Biography